Les effets de proximité dans l’appropriation collective d’un grand parc paysager à saguenay - Marie-Hélène Tremblay; Martin Simard (VertigO)
The idea to relate cities and nature has been a planning issue from the beginnings. During the XIX century, the implementation of large city parks such as Central Park in New York exemplifies that commitment. According to many, urban parks foster social relationships, create links to nature and help developing a collective identity, in other words, they improve quality of life for individuals and communities. Initially imagined and designed by planners, these public spaces in the middle of the cities are gradually adopted or not by residents and users, according to the adequacy between their characteristics and the needs of the population. In this context, we were interested in the neighborhood effects inside the sense of place development mechanisms. More precisely, we sought to verify the impact of distance between homes and parks on practices and representations. Our case study is related to the old port area of Chicoutimi in Saguenay. A survey was carried out among users. We thus could measure the influence of residential distance of parks to social representations of nature.